(untitled) (Global Journal of Human-Social Science, 2017)
Salinity is a complication towards evolving a sustainable food production system and habitat management throughout globe. Such problem has its origin from marine, geological and anthropogenic activities. Nature and properties of salinity has been reviewed on global extent with a view to its management in this regard.